A consultation training program for physicians for communication about complementary medicine with breast cancer patients: a prospective, multi-center, cluster-randomized, mixed-method pilot study. Issue 1 (December 2016) - Blödt, Susanne; Mittring, Nadine; Schützler, Lena; Fischer, Felix; Holmberg, Christine; Horneber, Markus; Stapf, Adele; Witt, Claudia
Abstract Background The aim was to develop and evaluate a training program for physicians for communicating with breast cancer patients about complementary medicine (CM). Methods In a cluster-randomized pilot trial eight breast cancer centers (two physicians per center) were randomized to either a complementary communication training program (9 h e-learning + 20 h on-site skills training) or to a control group without training. Each physician was asked to consult ten patients for whom he or she is not the physician in charge. We used mixed methods: Quantitative outcomes included physicians' assessments (empathy, complexity of consultation, knowledge transfer) and patients' assessments (satisfaction, empathy, knowledge transfer). For qualitative analyses, 15 (eight in the training and seven in the control group) videotaped consultations were analyzed based on grounded theory, and separate focus groups with the physicians of both groups were conducted. Results A total of 137 patients were included. Although cluster-randomized, physicians in the two groups differed. Those in the training group were younger (33.4 ± 8.9 vs. 40.0 ± 8.5 years) and had less work experience (5.4 ± 8.9 vs. 11.1 ± 7.4 years). Patient satisfaction with the CM consultation was relatively high on a scale from 0 to 24 and was comparable in the two groups (training group: 19.4 ± 4.6; control group 20.5 ± 4.1). The qualitative findings showed that physicians structured majority of consultations as taught during the training. Comparing only the younger and less CM experienced physicians, those trained in CM communication felt more confident discussing CM-related topics than those without training. Conclusion A CM communication-training program might be especially beneficial for physicians with less consulting experience when communicating about CM-related issues. A larger trial using more suitable quantitative outcomes needs to confirm this. Trial registration ClinicalTrials.gov:NCT02223091, date of registration: 7 February 2014.